2020
DOI: 10.3389/fenvs.2020.00075
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Functional Diversity in Vineyard Soils: Sulfur Metabolism and Links With Grapevine Plants and Wine Quality

Abstract: The quality of the vineyard soils has a direct impact on grapes and wine quality and represents a key component of the "Terroir concept." However, information on the impact of soil microbiota on grapevine plants and wine quality are generally lacking. In fact, over the last few years most of the attempts made to correlate soil microbial communities and wine quality were limited by overlooking both the functional traits of soil microbiota and the spatial variability of vineyards soils. In this work, we used a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
2
3
0
Order By: Relevance
“…However, GG management increased the Proteobacteria/Acidobacteria ratio in all plots (Tab.6), independently to the soil management, suggesting an improvement of soil nutritional status. This result confirms the key role of Proteobacteria in soil nutrient cycling in Sangiovese vineyards from Tuscany, as recently reported [35]. Fifteen different taxa of microarthropods were identified in the soil.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, GG management increased the Proteobacteria/Acidobacteria ratio in all plots (Tab.6), independently to the soil management, suggesting an improvement of soil nutritional status. This result confirms the key role of Proteobacteria in soil nutrient cycling in Sangiovese vineyards from Tuscany, as recently reported [35]. Fifteen different taxa of microarthropods were identified in the soil.…”
Section: Resultssupporting
confidence: 91%
“…The reduced copper applications in GG management gave in some years a higher downy mildew severity on leaves and clusters but no significant yield loss. The study showed no significant difference between a vineyard conducted with permanent grass or green manure, as found by other authors [35][36].…”
supporting
confidence: 84%
“…In this complex scenario, both composition and functions of soil biota are also significantly affected by soil features and their spatiotemporal heterogeneity, which makes it difficult to link specific soil microbial taxa to many soil processes (Fierer, 2017; Gottschall et al., 2021; Kuzyakov & Blagodatskaya, 2015; Mocali et al., 2020; Nemergut et al., 2013). As discussed later, spatial variability in distributions of soil microorganisms has been largely explored in the last decade (Delgado‐Baquerizo et al., 2018; Thompson et al., 2017).…”
Section: Soil Health and Soil Biologymentioning
confidence: 99%
“…An impetus toward this goal could derive from the field of microfluidics applications and tools like the “lab-on-chip” ( Aleklett et al, 2018 ) could have the potential to address some of the major challenges of tracking and monitoring of bioinoculants. The “lab-on-chip” (microarray) technology opens the avenue for the parallel, high-throughput multiple identification of target microorganisms and genes in environmental samples ( Wilson et al, 2002 ; Chandler et al, 2010 ; Schreiner et al, 2010 ; Mocali et al, 2020 ). Data obtained with amplification microarrays correlated well with conventional small subunit rRNA qPCR results ( Chandler et al, 2010 ).…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%